1996
DOI: 10.1139/v96-180
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental approaches to the effects of solvation on the small internal rotational potential of benzal fluoride

Abstract: Abstract:The internal rotational potential for benzal fluoride is computed at various levels of molecular orbital theory, including correlation-gradient, MP2 (frozen core) methods. The perturbations of the potential caused by solvents are calculated with the Onsager model (ellipsoidal cavity with I = 6 in the multipole expansion) as well as with the self-consistent isodensitypolarizable continuum model (SCI-PCM). Analysis of the 'H and "F nuclear magnetic resonance spectra in cyclohexane-'I,2 and acetone-d6 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…For an internal rotor as light as a vinyl group and for so low rotational barriers (Figure ), this is only a crude approximation. Consequently, in the case in hand, one may expect that rovibrational effects modify values of the involved NMR parameters. These effects can also be responsible for the previously observed deviations of δ­(H11), δ­(C11), and δ­(C12) from the regression lines and for apparently enhanced contribution of /2 and/3 orientations of the vinyl group.…”
Section: Resultsmentioning
confidence: 97%
“…For an internal rotor as light as a vinyl group and for so low rotational barriers (Figure ), this is only a crude approximation. Consequently, in the case in hand, one may expect that rovibrational effects modify values of the involved NMR parameters. These effects can also be responsible for the previously observed deviations of δ­(H11), δ­(C11), and δ­(C12) from the regression lines and for apparently enhanced contribution of /2 and/3 orientations of the vinyl group.…”
Section: Resultsmentioning
confidence: 97%
“…As stated above, determining the extent of charge delocalization from the phenoxide anion to the fluoromethyl group will be accomplished by removing the oxy anion, leaving benzyl fluoride. The examination of the solvent and ring substituent effects on these systems has the additional benefit of allowing for a comparison with an important series of papers by Schaefer and co-workers on the benzyl fluoride system. On the basis of calculations at the HF/6-31G(d)//HF/6-31G(d) and MP2/6-31G(d)//MP2/6-31G(d) levels and NMR studies, they have concluded that the preferred conformation in isolation for benzyl fluoride has the C−F bond oriented in the plane of the aromatic ring and the energetic maximum along the C(Ar)−CH 2 F rotational profile exists when the C−F bond is perpendicular to the ring. As will be shown below, the opposite energetic ordering is predicted when the basis set is augmented with diffuse functions.…”
Section: Introductionmentioning
confidence: 99%